(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
International conflicts are not a new event for humanity, since ancient times conflicts have caused negative effects on the individual, society and the whole world with damage, suffering, displacement and deprivation of security, safety and stability, as well as heavy material and human losses. International conflicts vary in terms of their nature, causes and objectives, as they vary from time to time, as with the passage of time, disputes become more complicated due to the development of the state and the development of its goals, interests, endeavors and motives. These conflicts have increased as a result of the development of the international community and the development of countries whose endeavors have become beyond their borders, especially countries with great influence and power to impose their control and opinion on other weak countries and extend their influence and hegemony, which leads to the occurrence of great tensions and political conflicts between countries that may lead to conflict, and as we know that within the borders of one state, almost no society is free from the occurrence of skirmishes and conflicts between individuals, groups, clans and political parties. These conflicts have widened their horizons to go beyond State borders between two or more members of the international community between states or entities and others. These conflicts, of course, have negative effects on security and safety at the level of ...